2021
DOI: 10.3390/ani11020521
|View full text |Cite
|
Sign up to set email alerts
|

The Association of an SNP in the EXOC4 Gene and Reproductive Traits Suggests Its Use as a Breeding Marker in Pigs

Abstract: In mammals, the exocyst complex component 4 (EXOC4) gene has often been reported to be involved in vesicle transport. The SNP rs81471943 (C/T) is located in the intron of porcine EXOC4, while six quantitative trait loci (QTL) within 5–10 Mb around EXOC4 are associated with ovary weight, teat number, total offspring born alive, and corpus luteum number. However, the molecular mechanisms between EXOC4 and the reproductive performance of pigs remains to be elucidated. In this study, rs81471943 was genotyped from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“…However, 10 QTL were found for the trait "Piglet Mortality". There was also no trait in the database defined as "Total litter weight within 3 weeks" (LW3W), but 1 QTL was listed for "Total litter weight at weaning" (He et al, 2021). There was also no QTL listed for Body Condition Score (BCS) or Shoulder Lesions (SHL).…”
Section: Genetic Architecturementioning
confidence: 99%
“…However, 10 QTL were found for the trait "Piglet Mortality". There was also no trait in the database defined as "Total litter weight within 3 weeks" (LW3W), but 1 QTL was listed for "Total litter weight at weaning" (He et al, 2021). There was also no QTL listed for Body Condition Score (BCS) or Shoulder Lesions (SHL).…”
Section: Genetic Architecturementioning
confidence: 99%
“…Moreover, several studies have reported that SNPs in intron were found relevant to production traits in pigs (such as litter size, backfat thickness, etc. ), which provided theoretical support and potential direction for further research [ 72 74 ]. This locus can predict the intramuscular fat content of pigs in an early, rapid, low-cost, and effective way, which could be used as a useful molecular marker for genetic breeding improvement of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent development of sequencing and genotyping tools for pigs have permitted the investigation of genomic evidence of selection and the discovery of potential genes linked with desired traits (He et al, 2021). For example, the bone morphogenetic protein receptor type 1B (BMPR-1B) gene in sheep may have foremost effect on their reproduction (Qi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%